Subunits of the GPI transamidase complex localize to the endoplasmic reticulum and nuclear envelope in Drosophila. Issue 7 (2nd March 2021) - Kawaguchi, Kohei; Yamamoto‐Hino, Miki; Matsuyama, Nina; Suzuki, Emiko; Goto, Satoshi
Abstract : A total of 10–20% of plasma membrane proteins are anchored by glycosylphosphatidylinositol (GPI). GPI is attached to proteins by GPI transamidase (GPI‐T), which contains five subunits named PIGK, PIGS, PIGT, PIGU, and GPAA1. We previously reported that PIGT localizes near the nucleus in Drosophila . However, localizations of the other four subunits remain unknown. Here, we show that a catalytic subunit of GPI‐T, PIGK, mainly localizes to the endoplasmic reticulum (ER), while the other four subunits localize to the nuclear envelope (NE) and ER. The NE/ER localization ratio of PIGS differs between cell types and developmental stages. Our results suggest that GPI‐T catalyzes GPI attachment in the ER and the other four subunits may have other unknown functions in the NE. Abstract :